Data‐Driven Investigation Reveals Subaerial Proportion of Basalts Since the Early Archean - Chun‐Tao Liu; Xiao‐Ming Liu; J. ZhangZhou (Geophysical Research Letters)
Abstract The subaerial exposure of the modern continental crust through time remains intensely debated, with estimates of the first exposure ranging from the late Archean to the Neoproterozoic. To constrain when and how much of the continental crust was exposed subaerially during Earth's history, we trained a supervised machine learning model on the compositions of modern subaerial and submerged basalts. Then, we applied this well‐trained model to a refined worldwide data set of basaltic compositions and calculated the mean proportions of basalts erupted subaerially since 3.8 billion years ago (Ga). Our results suggest that ∼20% of the basalts were exposed subaerially in the early Archean, which may have driven the synthesis of biopolymers crucial to the origins and evolution of life. The proportion of subaerial basalts increased markedly during two stages between the late Archean and the Paleoproterozoic before reaching the present‐day level no earlier than ∼1.8 Ga.